Modification of Polar Low Development by Orography and Sea Ice - Sergeev, D; Renfrew, IA; Spengler, T (Monthly Weather Review, 2018)
This is the final version. Available on open access from American Meteorological Society via the DOI in this record. The code used in this study relies on the iris Python package (Met Office 2016) and is available on GitHub (https://github.com/dennissergeev/mplosi). Model output data are available upon request. The life cycles of intense high-latitude mesoscale cyclones and polar lows are strongly shaped by their ambient environments. This study focuses on the influence of the orography of Svalbard and the sea ice cover in the Norwegian and Barents Seas on polar low development. We investigate two typical polar lows that formed near Svalbard during northerly cold-air outbreaks. Each case is simulated using the Met Office Unified Model with convection-permitting grid spacing. A series of sensitivity experiments is conducted with an artificially changed land mask, orography, and sea ice distribution. We find that Svalbard acts to block stably stratified air from the ice-covered Arctic Ocean, and as an additional source of low-level cyclonic vorticity aiding polar low genesis and intensification. A decrease in sea ice cover west of Svalbard results in a moderate intensification of the polar lows, particularly for the more convectively driven case, while an increase in the sea ice cover significantly hinders their development. These experiments exemplify that polar mesoscale cyclones in the northeast Atlantic can withstand large perturbations in the surface conditions (such as the removal of Svalbard) and still develop to sufficient intensity to be labeled as polar lows. However, there is a sensitivity to Svalbard’s orography and surrounding sea ice cover, illustrated by a clear modulation of polar low genesis and development. Natural Environment Research Council